Large spin diffusion length in an amorphous organic semiconductor - Shim, J. H.; Raman, K. V.; Park, Y. J.; Santos, T. S.; Miao, G. X.; Satpati, B.; Moodera, J. S. (AMER PHYSICAL SOC, 2008)
We directly measured a spin diffusion length (lambda(s)) of 13.3 nm in amorphous organic semiconductor (OS) rubrene (C42H28) by spin polarized tunneling. In comparison, no spin-conserved transport has been reported in amorphous Si or Ge. Absence of dangling bond defects can explain the spin transport behavior in amorphous OS. Furthermore, when rubrene barriers were grown on a seed layer, the elastic tunneling characteristics were greatly enhanced. Based on our findings, lambda(s) in single-crystalline rubrene can be expected to reach even millimeters, showing the potential for organic spintronics development.
Keywords: MAGNETORESISTANCE; STATES; METAL